Carbon-containing sintered body and manufacturing method thereof

By mixing carbon-containing materials with clay, granulating, and firing in a reducing atmosphere, the carbon-containing fired body achieves high durability and water absorption, addressing the limitations of the two-layer carbide fired body in Patent Document 1, and supports sustainable plant growth and carbon sequestration.

JP7606255B2Active Publication Date: 2024-12-25KANTOO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023522084
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-19
Publication Date
2024-12-25
Estimated Expiration
2041-05-19

AI Technical Summary

Technical Problem

The carbide fired body described in Patent Document 1 has a two-layer structure with a surface layer that does not contain carbide, leading to high water absorption and insufficient durability.

Method used

A carbon-containing fired body is produced by mixing a carbon-containing substance and clay, granulating the mixture, and then reducing and firing it in an oxygen-free atmosphere to achieve a specific gravity of 0.7 or less and a water absorption weight of 25% or more.

Benefits of technology

The solution ensures high durability and sufficient water absorption, enhancing carbon sequestration and reducing carbon dioxide emissions, while being cost-effective and suitable for growing a variety of plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606255000006
    Figure 0007606255000006
  • Figure 0007606255000007
    Figure 0007606255000007
  • Figure 0007606255000008
    Figure 0007606255000008
Patent Text Reader

Abstract

Provided are a ceramic structure and a production method for the ceramic structure that can ensure substantial water absorbency and high durability. This ceramic structure is formed by mixing a carbon-containing material and clay, granulating, and then reduction firing. The entirety of the ceramic structure from center to surface is reduced, and the ceramic structure has a bulk specific gravity of no more than 0.7 and a water absorption weight of at least 25%. The carbon-containing material is a wood material, the clay is bentonite, and the mixing ratio of the carbon-containing material and the clay is 20:80–35:65.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fired carbon-containing material obtained by mixing a carbon-containing material with clay, granulating the mixture, and firing the granulated mixture, and a method for producing the fired carbon-containing material. [Background technology]

[0002] In recent years, efforts to promote the Sustainable Development Goals (2030 Agenda for Sustainable Development, adopted at the United Nations Summit on September 25, 2015, hereafter referred to as "SDGs") have been underway on an international scale. Specifically, the SDGs include Goal 9: Create indispensable infrastructure for industry and technological innovation, Goal 12: Responsible consumption and production, Goal 13: Take urgent action to combat climate change, Goal 14: Protect and sustainably use water and its ecosystems, and Goal 15: Protect and sustainably use land, and there is a desire to develop technologies aimed at achieving these goals.

[0003] The technology described in Patent Document 1 is known as a technology that can contribute to achieving these goals. Patent Document 1 describes a sintered carbide body that is composed of a surface layer that is composed of clay and does not contain carbide, and an inner layer that is composed of clay and carbide, and a manufacturing method thereof. The sintered carbide body described in Patent Document 1 has good handleability because the carbide is not exposed on the surface, so that the hands do not get blackened when touched, and carbide fine powder does not scatter. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-12366 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the carbide sintered body described in Patent Document 1 has a two-layer structure consisting of a surface layer and an inner layer, and since the surface layer does not contain carbide, it tends to have excessively high water absorption, making it difficult to obtain sufficient durability.

[0006] The present invention has been made to solve the above-mentioned problems, and has an object to provide a carbon-containing sintered body that has high durability while ensuring sufficient water absorbency, and a method for producing the same. [Means for solving the problem]

[0007] The carbon-containing sintered body of the present invention is a carbon-containing sintered body obtained by mixing a carbon-containing material with clay, granulating the mixture, and then reducing and sintering the mixture, and is characterized in that the entire body from the center to the surface is reduced, has a bulk density of 0.7 or less, and has a water absorption weight of 25% or more.

[0008] In addition, the manufacturing method of the carbon-containing material sintered body of the present invention includes a mixing step of mixing a carbon-containing material with clay to form a mixture, a granulation step of forming the mixture into a clay-like form and then into granules, and a reduction firing step of firing the granulated mixture in a reducing atmosphere to form a carbon-containing material sintered body, characterized in that the reduction firing step reduces the entire mixture from the center to the surface to a bulk density of 0.7 or less and a water absorption weight of 25% or more. Effect of the Invention

[0009] According to the present invention, sufficient water absorbency and high durability can be ensured. [Brief description of the drawings]

[0010] [Figure 1] 1A to 1C are schematic diagrams illustrating a method for manufacturing a ceramic structure according to a first embodiment of the present invention. [Diagram 2] 5A to 5C are schematic diagrams illustrating a method for manufacturing a ceramic structure according to a second embodiment of the present invention. [Diagram 3]5A to 5C are schematic diagrams illustrating a method for manufacturing a ceramic structure according to a third embodiment of the present invention. [Figure 4] FIG. 11 is a diagram showing the results of fluorescent X-ray analysis of the ceramic structure according to Example 3 of the present invention. [Diagram 5] FIG. 13 is a diagram showing the results of fluorescent X-ray analysis of a conventional ceramic structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (First embodiment) Hereinafter, an embodiment of the present invention will be described.

[0012] [structure] An embodiment of the present invention will be described with reference to the drawings. As shown in FIG. 1, a ceramic structure which is a sintered carbon-containing material according to one embodiment of the present invention is formed into a roughly spherical shape having a diameter of, for example, about 4 mm, and a plurality of the ceramic structures are used as soil (compost) for growing plants.

[0013] This ceramic structure is composed of a mixture of sawdust (a carbon-containing wood material) made by crushing pieces of wood (wood material) such as cedar or cypress into sawdust-like form, and bentonite (clay), for example, and the sawdust and bentonite are mixed in a weight ratio of 20:80 to 35:65, preferably 29:71 to 32:68, and more preferably 30:70.

[0014] The sawdust is made of fine wood powder, for example, about 200 to 400 mesh, and has a carbon content of about 50%. Note that the sawdust may contain trace amounts of wood chips of other trees, such as pine, other than cedar and cypress.

[0015] Here, if the mixing ratio of bentonite to sawdust is 65 or less, the mixture of sawdust and bentonite cannot be granulated. Also, if the mixing ratio of bentonite to sawdust is 80 or more, the mixture will simply become ceramic balls, and the effect of the sawdust cannot be expected.

[0016] This ceramic structure is formed by kneading the mixture while adding water, forming a granular mixture with a diameter of about 4 mm having a smooth surface shape, drying it until the moisture content is 8% or less, preferably 5% or less, and then firing the granular mixture until it is completely reduced. This ceramic structure is configured so that the bulk density after firing is 0.7 or less, preferably 0.6 or less, specifically in the range of 0.57 to 0.63, and the water absorption weight is 25% or more, preferably 30% or more, and has a similar configuration to so-called terra preta (black soil of the Amazon). Here, the water absorption weight is the weight ratio (%) of the weight before absorbing water (weight before water absorption) to the weight after absorbing water (weight absorbed).

[0017] If the bulk density of the ceramic structure after firing is less than 0.56, the strength after firing will be insufficient, and if the bulk density of the ceramic structure after firing is more than 0.63, the water absorption rate will tend to be too low. Also, if the water absorption rate of the ceramic structure is less than 25%, the water absorption rate will be too low and the ceramic structure will become too dry, making it unsuitable for growing plants.

[0018] [Manufacturing method] Next, a method for manufacturing the ceramic structure according to the above embodiment will be described with reference to FIG.

[0019] (1)Mixing process First, sawdust is prepared as a carbon-containing material (wood material) and bentonite is prepared as clay (ceramic), and the sawdust and bentonite are mixed in a weight ratio of 20:80 to 35:65, preferably 29:71 to 32:68, and more preferably 30:70. Then, the mixed sawdust and bentonite are mixed to obtain a mixture.

[0020] (2) Mixing process (first granulation process) Next, water is added to the mixture and kneaded until the water content of the mixture reaches about 30%, and then while kneading with a clay kneader, the mixture is extruded under its own weight from a cylindrical extrusion hole of about 4 mm in diameter in an extruder (pelletizer) to form a cylinder with a diameter of about 4 mm.

[0021] (3) Granulation process (second granulation process) The mixture of multiple cylindrical bodies is subjected to a granulation process (granulation treatment) using a granulator for about 6 to 15 minutes, preferably about 12 to 15 minutes, and more preferably about 14 to 15 minutes, to produce a granular mixture with a smooth surface and a diameter of about 2.5 mm to 4.3 mm, preferably about 4 mm.

[0022] (4) Drying process A plurality of granular mixtures are placed on a sieve or the like, arranged on the sieve, and dried in the sun until the moisture content of each granular mixture is 8% or less, preferably 5% or less. Note that this drying process can also be performed by mechanical drying, in which hot air is blown onto the granular mixture using a burner, for example.

[0023] (5) Reduction firing process The dried granular mixture is placed in a cylinder, for example, 30 cm in diameter x 30 cm in height, and then this cylinder, etc. is placed in a firing kiln (for example, a pottery kiln, etc.) together with the multiple granular mixtures, and the multiple granular mixtures are fired for reduction at a temperature of 450°C or higher and 550°C or lower, preferably 450°C or higher and 500°C or lower, and more preferably about 480°C, for 4.5 to 6.0 hours, preferably 5.5 hours, in an atmosphere free of oxygen (reducing atmosphere), in other words, in a reducing state (oxygen-free state), so that almost all parts of each of the multiple granular mixtures from the center to the surface are reduced and the pH after firing does not increase (so that it becomes weakly acidic suitable for plant growth).

[0024] Here, in the reduction firing process, the mixture of sawdust and bentonite is fired in an oxygen-free atmosphere, i.e., reduction firing is performed, so that carbon itself, not carbon compounds, is reduced and fired. In this reduction firing, cellulose (C6H 10 O5) n , hemicellulose (C5H8O4) n Furthermore, since the lignin is decomposed and carbonized, the carbonized material becomes inorganic carbon rather than organic carbon, making it possible to form a ceramic structure that will not decompose for a long period of time.

[0025] Here, the firing temperature and firing time in this reducing state can be appropriately adjusted to produce a ceramic structure that matches the soil pH of the plant to be grown. If necessary, the surface of the fired granular mixture can be oxidized by firing in an aerobic state at 800 to 900°C for about 5 to 6 minutes using a sheath heater or at about 1000°C using a gas burner.

[0026] (6) Cooling process Thereafter, the fired granular mixture is removed from the firing kiln and allowed to cool naturally, thereby forming a desired ceramic structure.

[0027] Second embodiment Next, a second embodiment of the ceramic structure according to the present invention will be described with reference to Fig. 2. This second embodiment is an embodiment that does not require the granulation step (second granulation step) of the first embodiment, and changes the water content in the kneading step (2) and the shape of the extrusion hole of the extruder (pelletizer). Specifically, the extruder used in this second embodiment has an extrusion hole formed in the shape of a funnel whose diameter decreases concentrically downward. The extrusion hole is configured so that the inner diameter dimension at the lower end is about 4 mm.

[0028] (2A) Kneading process (granulation process) The mixture mixed in the above (1) mixing step is kneaded while adding water until the water content reaches about 10 to 20%, preferably about 15%, and then kneaded using a clay kneader, and the mixture is then extruded from the funnel-shaped extrusion hole of an extruder (pelletizer) to form a cylinder with a diameter of about 4 mm. At this time, since the water content of this cylinder is set low, at about 10 to 20%, preferably about 15%, in addition to the (3) granulation step (second granulation step) according to the first embodiment, the (4) drying step is also unnecessary.

[0029] (5A) Reduction firing process The plurality of cylindrical bodies manufactured in the above (2A) kneading step (granulation step) are then subjected to reduction firing in the same manner as in the (5) reduction firing step according to the first embodiment.

[0030] (6A) Cooling process Thereafter, the fired cylindrical body is removed from the firing kiln and allowed to cool naturally, thereby forming a desired ceramic structure.

[0031] Third embodiment Next, a ceramic structure according to a third embodiment of the present invention will be described with reference to Fig. 3. In this third embodiment, the configuration of the (2) kneading step (first granulation step) according to the first embodiment is modified.

[0032] (2B) Kneading process (first granulation process) The mixture mixed in the above (1) mixing step is kneaded while adding water until the water content reaches about 30%, then kneaded using a clay kneader, and then molded into a plate-like body with a thickness of about 4 mm. Then, a part of this plate-like body is chipped off in the thickness direction, for example, in widths of about 4 mm, to form a granular body with a width of about 4 mm.

[0033] (3B) Granulation process (second granulation process) Thereafter, these multiple granules are subjected to a granulation process (granulation treatment) similar to the granulation process (second granulation process) (3) according to the first embodiment described above, to produce a granular mixture with a smooth surface and a diameter of approximately 2.5 mm to 4.3 mm, preferably about 4 mm.

[0034] This granular mixture is then subjected to the same processes as those of the first embodiment, namely (4) drying step, (5) reduction firing step, and (6) cooling step, to form a desired ceramic structure.

[0035] (Fourth embodiment) Next, a fourth embodiment of the ceramic structure according to the present invention will be described. In this fourth embodiment, the configurations of the (2) kneading step (first granulation step) and (3) granulation step (second granulation step) in the first embodiment are changed, and the use of an extruder (pelletizer) in the (2) kneading step (first granulation step) is eliminated.

[0036] (2C) Kneading process (first granulation process) Water is added to the mixture obtained in the above mixing step (1) while mixing until the water content of the mixture reaches about 20%, and the mixture becomes somewhat cohesive, in other words, crumbly.

[0037] (3C) Granulation process (second granulation process) Thereafter, a predetermined amount of this crumbly mixture is placed in a granulator and granulated (pelletizing) while, for example, spraying mist of water using a spray bottle or the like to replenish the mixture, to produce a granular mixture with a smooth surface and a diameter of approximately 2.5 mm to 4.3 mm, preferably about 4 mm.

[0038] This granular mixture is then subjected to the same processes as those of the first embodiment, namely (4) drying step, (5) reduction firing step, and (6) cooling step, to form a desired ceramic structure.

[0039] [Effects] In the ceramic structures according to the above embodiments, the sawdust and bentonite are mixed in a weight ratio of 20:80 to 35:65, preferably 29:71 to 32:68, and more preferably 30:70. As a result, the sawdust ratio can be increased compared to conventional ceramic structures, and the carbon ratio can be increased, thereby enhancing the carbon isolation effect.

[0040] Furthermore, by increasing the sawdust ratio by 5%, the carbon sequestration effect can be increased by 20%. Therefore, by growing plants in pots covered with the ceramic structure, the plant's growth capacity can be improved, and it is possible to grow a wide variety of plants by using only this ceramic structure. In addition, since the method of use is very simple, anyone with basic knowledge of growing plants can achieve similar growth results. In particular, germination tests using watercress were also successful.

[0041] In addition, the dried granular mixture is fired under reducing conditions, and all parts of the granular mixture from the surface to the center are reduced and fired to carbonize it, so that the granular mixture after firing can have the same strength from the surface to the inside, thereby increasing the strength of the entire manufactured ceramic structure.

[0042] As a result, the cracks in the produced ceramic structure can be reduced, and durability can be ensured. At the same time, the entire granular mixture is reduced from the center to the surface. This makes it possible to achieve carbon minus compared to the amount of carbon dioxide used for production, and semi-permanent carbon sequestration (carbon neutrality) is possible, which is expected to have a global warming prevention effect, making it possible to use it as compost for reducing global warming.

[0043] In particular, the possibility of semi-permanent carbon sequestration will enable a reduction in carbon dioxide emissions, which will help achieve five of the 17 SDGs, namely Goal 9: Create resilient infrastructure for industry and technological innovation, Goal 12: Responsible consumption and production, Goal 13: Take urgent action to combat climate change, Goal 14: Protect and sustainably use water and marine life, and Goal 15: Protect and sustainably use land.

[0044] In addition, since the ceramic structure is entirely reduced from the center to the surface, it is not biodegradable, which can suppress the emergence of pests during use and allows it to be used indoors. Therefore, although it can be used outdoors, such as cherry blossoms and pansies, it can also be used safely indoors.

[0045] At the same time, by reducing the entire granular ceramic structure from the center to the surface, the structure has a moderate water absorption, but the capillary phenomenon is suppressed, so the water absorption does not tend to decrease even with long-term use, making it suitable for growing plants. In particular, since the water absorption can be suppressed while maintaining the water retention, the ceramic structure inside the pot can be kept slightly dry even if the surface of the pot is frequently watered, so the growth of algae and moss on the surface of the pot and the ceramic structure can be reduced.

[0046] The kneaded mixture is kneaded in a clay kneader and then granulated in a marumerizer, so the mixture can be granulated without requiring a relatively large-scale device for the granulation process, thereby significantly reducing production costs.

[0047] Furthermore, since the granular mixture is dried in the sun before firing, the possibility of the granular mixture exploding during firing can be reduced, and firing can be performed using a firing kiln of the same size as is typically used for pottery, the costs required for the drying and firing processes can be significantly reduced compared to forced drying and firing, which typically require large-scale equipment. In particular, by using hot air with an electric heater for the drying process and an electric firing kiln for the firing process, and using electric equipment (all-electric), it becomes possible to manufacture ceramic structures without using carbon dioxide.

[0048] At the same time, by making it possible to fire the granular mixture in a firing kiln the size of a pottery kiln, it is possible to carry out the firing process in small lots, enabling small-scale production and reducing costs. In this firing process, the entire granular mixture is reduced from the center to the surface, so powder falling off from the granular mixture that may occur during firing can be almost completely eliminated.

[0049] The produced ceramic structure has pores of a size that easily adsorbs microorganisms, and also tends to contain a large amount of impurities, making it suitable for growing plants.

[0050] In addition, by mixing the ceramic structure into soil after use and using it to grow plants, it is possible to achieve the 3Rs of this ceramic structure (reuse: repeated use, reduce: no disposal required, recycle: use as a soil conditioner after use).As it is composed only of carbon-containing materials and clay, it can be disposed of as general waste (combustible waste), making it easy to dispose of.

[0051] In short, conventional ceramic structures require large capital expenditures of around 100 million yen to manufacture, and because sales destinations are extremely limited, there was no prospect of demand even if the facilities were operated at full capacity.

[0052] In contrast, in the ceramic structure of the present application, the granulation method is changed from a method using a kneader to a method using a clay kneader, and the firing method is changed from a method using a kiln with a size of about 10 m and a cooling kiln with a size of about 7 m to a method using a firing kiln with a size of about a pottery kiln. This eliminates the possibility of the granular mixture exploding during firing, and allows the drying process to be done in the sun, making it possible to produce small quantities at low cost.

[0053] [Example 1] Next, Example 1 of the ceramic structure according to the present invention will be described. In this Example 1, the various values ​​of the ceramic structure manufactured by the above-mentioned manufacturing method were measured. The average values ​​of the various values ​​of the ceramic structure are shown in Table 1.

[0054] In Table 1, "2t" is the average value of the results of measuring a total of 2t of ceramic structures multiple times, and "test" is the average value when the operating time of the malmerizer in the granulation process was changed to 6 minutes, 7 minutes, 12 minutes, and 13 minutes.

[0055] In particular, among the measured values, "bulk density before firing" is the weight per cc of the granular mixture before firing. "Weight before firing" is the weight of the entire granular mixture fired at one time, and "weight after firing" is the weight of the granular mixture fired at one time. "Weight reduction rate" is -{("weight after combustion" - "weight before combustion") / "weight before combustion"} x 100, and "total bulk density after firing / cc" is the bulk density (cc) of the entire granular mixture fired at one time.

[0056] Furthermore, the "bulk density after firing" is "total bulk density after firing / cc" / "weight after firing." Also, the "weight immediately after water absorption" is the weight per 100cc of the granular mixture fired at once after it is submerged in water for 3 minutes, and the "absorbed weight" is "weight immediately after water absorption" - "bulk density after firing / 100cc." Furthermore, the "absorbed weight of water absorption ratio" is "absorbed weight" / "bulk density after firing / 100cc" x 100, and the "total absorbed ratio" is "absorbed weight" / "weight immediately after water absorption" x 100.

[0057] [Table 1]

[0058] In the above Example 1, a total of 2 ton of ceramic structures were measured multiple times, and the respective values ​​were as follows.

[0059] [Table 2]

[0060] In addition, in the above Example 1, when the operating time of the malmerizer in the granulation process was changed to 6 minutes, 7 minutes, 12 minutes, and 13 minutes, the respective values ​​were as follows.

[0061] [Table 3]

[0062] Furthermore, when the operating time of the Marmerizer was shortened, several ceramic structures were found to be easily crushed after firing, and therefore it was found that it is preferable to extend the operating time of the Marmerizer, for example to 12 minutes or more.

[0063] [Example 2] Next, a description will be given of Example 2 of the ceramic structure according to the present invention. In this Example 2, the carbon content of the ceramic structure produced by the above-mentioned production method was measured by combustion analysis.

[0064] The ceramic structure was then measured by the Japan Food Analysis Center, a general incorporated association, who used a measuring device, the Vario EL cube elemental analyzer (Elementar), and the carbon content was found to be 10.6% by organic elemental analysis.

[0065] On the other hand, the carbon content of the ceramic structure manufactured by the conventional method according to the above-mentioned Patent Document 1 was measured using a similar measuring device, and the carbon content by organic element analysis was only 3.8% (Analysis Test Report: No. 201193150001-0101). Therefore, it was found that the ceramic structure according to the present invention can greatly improve the carbon ratio as described above, and can dramatically increase the carbon isolation effect.

[0066] [Example 3] Next, in Example 3 of the ceramic structure according to the present invention, the carbon content of the ceramic structure is measured by X-ray fluorescence analysis. Specifically, when the carbon content of this ceramic structure was requested to Gunma Prefectural Industrial Technology Center, the carbon content measured by X-ray fluorescence analysis was 20.5403%, as shown in Fig. 4. On the other hand, the carbon content of the ceramic structure manufactured by the conventional method according to the above-mentioned Patent Document 1 was only 17.2485%, as shown in Fig. 5 (Test Results Notification: Gunma Prefectural Industrial Technology Center No. 2304-648).

[0067] The above-mentioned X-ray fluorescence analysis was performed using a wavelength dispersive X-ray fluorescence analyzer (XRF-1700: manufactured by Shimadzu Corporation), and the X-ray conditions were as follows: the target material of the X-ray tube was Rh, the tube voltage was 40 kv, the tube current was 95 mA, the atmosphere of the X-ray passage was a vacuum of 30 Pa or less, and the analysis diameter (aperture) was 10 mmφ. In this analysis, the measurement object was broken and mixed in a mortar, and tablets were made by a hydraulic press using a vinyl chloride ring for pressure molding as a holder, and the tablets were measured as the measurement sample.

[0068] [Example 4] Next, Example 4 of the ceramic structure according to the present invention will be described. In Example 4, the firing temperature in the firing step when manufacturing the ceramic structure by the above-mentioned manufacturing method is changed. The numerical values ​​of the ceramic structure in which the firing temperature is changed are shown in Table 4.

[0069] [Table 4]

[0070] As a result, as shown in Table 4, although there is an error due to the difference in the firing amount in the firing step, the water absorption weight of the ceramic structure can be made 30% or more by firing at a higher temperature. However, in order to make the bulk density after firing (bulk density after firing) 0.7 or less, preferably 0.6 or less, specifically in the range of 0.57 to 0.63, and to make the pH after firing weakly acidic (about 6.5), it was found that a firing temperature of 550°C or less, preferably 500°C or less, and more preferably 480°C is suitable. Therefore, it was found that the firing temperature in the reduction firing step of the ceramic structure is 550°C or less, preferably 500°C or less, and more preferably about 480°C.

[0071] In Example 4, the strength of the ceramic structures fired at each firing temperature, i.e., the brittleness and crushability of the surface, were tested. In this test, a predetermined amount of the ceramic structures produced at each firing temperature and water were placed in a predetermined test bottle, and the test bottle was stoppered and vigorously shaken, and the water in the test bottle was replaced three times, left for two hours, and then vigorously shaken, and the cloudiness of the water in the test bottle was confirmed (suspension test).

[0072] At the same time, the ceramic sintered bodies manufactured at each sintering temperature were immersed in water and the presence or absence of water absorption sounds and floating objects were checked immediately after immersion, and the ceramic sintered bodies immediately after immersion and those after immersion for a specified time, for example 2 hours, were placed on a crush confirmation plate and crushed to check the feel. The results are shown in Table 5.

[0073] [Table 5]

[0074] Therefore, as shown in Table 5, when the firing temperature was 400° C., the ceramic structure produced gave off a water absorption sound immediately after immersion in water and had no floating objects. However, the ceramic structures immediately after water absorption and after a predetermined time had such strength that a single grain could be crushed by pinching it between fingers (short grain finger pressure crushing).

[0075] In addition, in the suspension test, when the ceramic structure and water were placed in a test bottle and vigorously shaken, suspension was observed, but when the water in the test bottle was changed three times, left for two hours, and then vigorously shaken, almost no suspension was observed.

[0076] Next, in the case of a firing temperature of 450°C, the ceramic structure could make a water absorption sound immediately after immersion in water and had no floating objects. However, the ceramic structure immediately after absorbing water could not be crushed by pinching it with fingers (short grains cannot be crushed by finger pressure), but it could be crushed by pinching it with a fingernail. After a certain time had passed since immersion in water, the strength was good, but as time passed, the strength decreased to the point where it could be crushed with a small force.

[0077] In addition, in the suspension test in this case, the ceramic structure was confirmed to be slightly suspended in both cases when it was placed in a test bottle and vigorously shaken with water, and when the water in the test bottle was changed three times, left for two hours, and then vigorously shaken.

[0078] Next, in the case of the firing temperature of 480°C, the sound of water absorption could be confirmed immediately after immersion in water and no floating objects were present in the ceramic structure. However, the ceramic structure immediately after absorbing water could not be crushed by pinching it with fingers (short grains cannot be crushed by finger pressure), but after a certain amount of time had passed since immersion in water, although there was no problem with its strength, it was strong enough that it could be crushed with less force than immediately after absorbing water.

[0079] In addition, in the suspension test, the ceramic structure was hardly suspended when placed in a test bottle and vigorously shaken with water, and when the water in the test bottle was changed three times, left for two hours, and then vigorously shaken.

[0080] Next, in the case of a firing temperature of 500°C, the ceramic structure could make a water absorption sound immediately after immersion in water and had no floating objects. However, the ceramic structure immediately after absorbing water could not be crushed by pinching it with fingers (short grains cannot be crushed by finger pressure), but after a certain amount of time had passed since immersion in water, although there was no problem with its strength, it was strong enough that it could be crushed with less force than immediately after absorbing water.

[0081] In addition, in the suspension test, the ceramic structure was hardly suspended when placed in a test bottle and vigorously shaken with water, and when the water in the test bottle was changed three times, left for two hours, and then vigorously shaken.

[0082] Furthermore, when the firing temperature was 550°C, the ceramic structure was able to make a water absorption sound immediately after immersion in water and no floating objects were present. However, the ceramic structure immediately after absorbing water could not be crushed by pinching it with fingers (short grains cannot be crushed by finger pressure), but after a certain amount of time had passed since immersion in water, although there was no problem with its strength, it was strong enough that it could be crushed with less force than immediately after absorbing water.

[0083] In the suspension test, almost no suspension was observed when the test bottle was placed in the test container and vigorously shaken with water, and when the water in the test bottle was changed three times, left for two hours, and then vigorously shaken.

[0084] From the above, it was found that in the reduction firing step when manufacturing a ceramic structure, in order to achieve a post-sintering bulk density of 0.7 or less, preferably 0.6 or less, a firing temperature of preferably 500° C. or less, more preferably 480° C. or less is suitable. Also, it was found that the firing temperature in the reduction firing step is preferably 450° C. or more, in terms of the strength of the fired ceramic structure.

Claims

1. A carbonaceous material fired body for growing plants, which is made by mixing a carbonaceous material and clay, granulating the mixture, and then reducing and firing the mixture, The entire surface is reduced from the center to the surface. The bulk density is 0.7 or less, Water absorption is 25% or more. A sintered carbon-containing body.

2. The bulk density is 0.57 to 0.

63.

2. The sintered carbon-containing material according to claim 1.

3. the carbon-containing material is a wood material, The clay is bentonite; The mixing ratio of the carbon-containing material to the clay is 20:80 to 35:65; 3. The sintered carbon-containing material according to claim 1 or 2.

4. A method for producing a carbon-containing sintered body for growing plants, comprising: A mixing step of mixing a carbon-containing material and clay to form a mixture; A granulation step of forming the mixture into a clay-like form and then granulating it; a reduction-sintering step of sintering the granulated mixture in a reducing atmosphere to obtain a carbon-containing sintered body; Equipped with The reduction and firing step reduces the entire mixture from the center to the surface to a bulk density of 0.7 or less and a water absorption density of 25% or more. A method for producing a sintered carbon-containing material, comprising:

5. The mixing step is performed in such a manner that the mixing ratio of the carbon-containing material to the clay is 20:80 to 35:

65. The method for producing a sintered carbon-containing material according to claim 4 .

6. the carbon-containing material is a wood material, The clay is bentonite. The method for producing a sintered carbon-containing material according to claim 4 or 5.

Citation Information

Patent Citations

  • Production of tile changed in color after firing

    JP1994157124A

  • Production of silicon carbide ceramics

    JP1998194837A

  • Granular sintered body and its manufacture

    JP1998258228A

  • Hybrid type carbide

    JP2001220235A

  • Method for purifying liquid waste generated when wood is sawed

    JP2002159971A